Decision Support System for Choosing the Best Mechanic Using the Smart Method at Cv. Garuda Mas Motor Binjai - Manik , Yolanda Arta Sabrina; Fauzi, Achmad; Khair, Husnul (Devitara Innovations, 2024)
Mechanics are the most important asset in an automotive company, workshop mechanics are responsible for the maintenance and repair of motor vehicles when damage occurs. However, not only dealing with damage, mechanics also conduct thorough checks before damage to customers' vehicles occurs. To be able to provide satisfaction with vehicle maintenance services or motorcycle services, of course CV. Garuda Mas Motor Binjai must have good and reliable mechanics. So that customers will feel satisfied with the service provided by the Dealer. To obtain the best mechanic, of course, an assessment must be carried out on the mechanics who will work. Usually this assessment is carried out by the Dealer only by conducting direct testing on a case of damage problems without considering anything else. So that in some cases there are mechanics that are not in accordance with the qualifications desired by the Dealer. For this reason, it is necessary to build a decision support system that can help the Dealer in selecting the best mechanic on the CV. Garuda Mas Motor Binjai. From the data on the criteria for selecting the best mechanic, the results of the analysis of the SMART method from the 20 alternative data above, it can be seen that the one who obtained the best score or ranking is the mechanic on behalf of Suriono with the results of the analysis using the SMART method 0.85.